Adapting business practices to new realities in the middle of a crisis: First findings from the COVID-19 European company survey - Jasper van Loo; Franz F. Eiffe; Gijs van Houten (Publications Office of the European Union, 2021)
This working paper presents the first findings of a survey on the impact of COVID-19 on workplace practices among employers in EU Member States. The survey was developed, organised and fielded at end-2020 by Eurofound and Cedefop. It explores the impact of the health crisis on companies in the EU-27 and sheds light on how employers reacted to it. As well as reporting on changes to core business activities, infrastructure and work organisation, the paper provides new insight into how the pandemic affected jobs and skills needs, and how employers reacted to such changes.
Keywords: 370; Coronavirus; Beschäftigungseffekt; Unternehmenspolitik; Arbeitsorganisation; Arbeitsgestaltung; Betriebliches Bildungsmanagement; EU-Staaten